Front Cover: Wide‐field time‐gated photoluminescence microscopy for fast ultrahigh‐sensitivity imaging of photoluminescent probes (J. Biophotonics 8/2016). Issue 8 (2nd August 2016) - Razali, Wan A. W.; Sreenivasan, Varun K. A.; Bradac, Carlo; Connor, Mark; Goldys, Ewa M.; Zvyagin, Andrei V.
Abstract : The ultimate limit of an imaging system based on photoluminescent molecular‐probes is set by the signal‐tonoise ratio between the bio‐probes and the background. A microscopy technique which combines nanoruby photoluminescent bio‐probes and time‐gating acquisition is proposed in order to achieve manifold improvement on imaging contrast capabilities. The system is sensitive and fast enough to image single nanoruby particles within cultured cells as well as to capture the particle‐binding kinetics in biological fluids. Further details can be found in the article by Wan A. W. Razali et al. on pp.848–858 .